Estrogen receptor gene polymorphisms and alveolar bone loss in postmenopausal Malay women - Swaminathan, D.; Haslina, T.; Rehman, A.; Ahmad, A. (2012)
Objectives: To investigate the distribution of estrogen receptor gene (ERG) polymorphisms in postmenopausal Malay women(PMW) and to find the association between the polymorphisms and alveolar bone loss. Design: This is a cross-sectional study on 64 PMW recruited from the Out Patient Dental Clinic, Hospital Universiti Sains Malaysia, Kelantan, Malaysia. Materials and Methods: Oral examinations were performed on all subjects and alveolar bone loss was measured from Orthopanthomogram radiographs. Genomic DNA was extracted from venous blood samples of each subject. Determination of estrogen receptor genotyp€s was performed by polymerase chain reaction. Subsequently, restriction fragment length polymorphism (RFLP) technique was employed to profile the ERG polymorphisms where the restriction cleavages of amplified ERG were cut using the two restriction enzymes, PvuII and XbaI. Estrogen receptor genotypes were represented as P or p for PvUII and X or x for XbaI with the lower case letters signifying the presence of the restriction site. Results: This study indicated a high frequency of heterozygous allelic variant (PpXx) in PMW. However no significant association between ERG polymorphisms and alveolar bone loss was observed. Conclusions: Within the limitation of study, ERG polymorphisms may not be a genetic marker for the alveolar bone loss in postmenopausal women subjects used in this study.